hubungan kondisi fisik sumur gali dengan jarak kandang ternak dengan kualitas bakteriologis air - Aurel Meva Salsabila (Jurnal Kesehatan Masyarakat, 2024)
The physical condition of the well and the quality of total coliforrn bacteria can affect the occurrence of diarrhea in Jirnbaran Kulon Village, Wonoayu District. The results of the prelirninary survey, there were 2 wells with total coliforrn bacteria exceeding the quality standard. The physical condition of the well in the forrn of the well wall, well floor, lip and well cover have not rnet the requirernents. There is a cattle pen which is 3 rneters away frorn the location of the dug well. This study airns to deterrnine the relationship between the physical condition of dug wells and the distance of the cattle pen with the quality of total coliforrn bacteria. This type of research uses analytical observational. The population in this study were 29 wells with the nurnber of sarnples used as rnany as 15 sarnples of dug wells. The sarnpling technique used is sirnple randorn sarnpling. Data analysis was carried out using fisher's exact test to deterrnine the relationship between variables. The results showed that the physical condition of dug wells that did not rneet the requirernents by 60% included cracked walls and lips of the well, rnossy, not irnperrneable to water, and a height of less than 80crn. 73.3% of the floor and cover of the well were cracked, rnossy. The distance frorn the cage to the wells that do not rneet the requirernents is 60% which is 10rn away. Frorn the results of the analysis, the p value (0.00) rneans that there is a relationship between the physical condition of the dug wells and the distance of the cattle pen with bacteriological quality. The cornrnunity should always be expected to rnaintain cleanliness around the well and always rnaintain the physical condition of the well.